A systematic review identifying outcomes and outcome measures in Dupuytren's disease research. (June 2020) - Karpinski, Marta; Moltaji, Syena; Baxter, Charmaine; Murphy, Jessica; Petropoulos, Jo-Anne; Thoma, Achilleas
This systematic review summarizes the outcome reporting standards in Dupuytren's disease treatment research. A search of Ovid Medline, Ovid Embase, and CINAHL was conducted. Randomized controlled trials, cohort studies, and case series published between 1997 and 2017, investigating treatment of Dupuytren's disease with fasciectomy, fasciotomy, or collagenase, were eligible for inclusion. Range of motion was the most commonly reported outcome, appearing in 77% of included studies. Outcomes, such as range of motion, recurrence, and clinical success, were frequently defined, however many different definitions were used. We identified 37 unique measurement methods for range of motion, 28 for recurrence, and 25 for clinical success. Most outcomes were assessed at multiple time points, and only a few studies reported results according to established clinical significance thresholds. Development of a core outcome set will help standardize outcome reporting, and ensure future research in this field is relevant, interpretable, and amenable to systematic review and/or meta-analysis.